Integrating and infusing of Islamic values in the existing engineering course subject: A case study - Ahmad, Zuraida (2011)

(untitled)
This paper presents the approach by the author in implementation of Islamisation of human knowledge through integrating the Islamic values with engineering subjects. The theoretical concepts of Islamisation of human knowledge in engineering education have been presented and published in so many conferences and articles, however some are found too philosophical in nature that made ordinary technologist and/or engineering educators have difficulties to understand and implement. Questions that always arise; what are the problems that militate against execution of the Islamization programme in engineering education? And, what roles can Islamic educators (murrabbies) play in order to ensure the accomplishment of the Islamization of engineering knowledge? The case study reported in this paper is an example of author’s trial in integrating the Islamic values into the existing engineering subject with the aim to develop students upon graduation will have the ‘ilm, iman, amal and akhlaq; and at the same time indirectly answering the two above-mentioned questions.